Third-Party Litigation Funding - Zokaitė, Justina (Teisė, 2026)
The article analyzes the concept of third-party litigation funding and its limitations. The study aims to consistently identify the essential features of this form of dispute financing and, by analyzing them, to conceptually reveal the essence of third-party litigation funding in commercial litigation. The article identifies four essential features of third-party litigation funding: coverage of litigation costs, provision of financing by an external entity unrelated to the parties to the dispute, remuneration for financing, and a conditional return for the funder depending on the outcome of the case. It is emphasized that, due to the variety of dispute financing models that exist in practice, these characteristics must be interpreted systematically, while taking into account the specific factual circumstances, as well as the purpose and nature of the financing. It is concluded that a clear distinction between commercial and non-commercial funding is a necessary condition for consistent risk assessment and proportionate regulation of this institution.
Keywords: third-party litigation funding; dispute funding; civil procedure; litigation costs